Network learning and interorganizational learning: a theoretical framework of relationship and interdependence - Julieta Kaoru Watanabe-Wilbert (Cadernos EBAPE.BR, 2022)
“Interorganizational learning” (IOL) and “network learning” (NL) are still frequently interpreted as if they were the same phenomenon, even though Knight (2002) claimed they are different constructs. This study demonstrates the consistency of Knight’s claim based on the analysis of both learning processes. Moreover, it highlights their differences in understanding the constructs in the scope of interorganizational networks and organizational transformations. Based on an integrative review, this article describes the subprocesses of IOL and NL through a multilevel learning lens. As a result, the authors develop five propositions and a theoretical framework showing that IOL and NL are indeed different constructs, and the former is an antecedent of the latter. By being aware of the differences between the two constructs, managers may allocate resources and energy easier to achieve organizational change or network-wide transformation. Moreover, the paper presents the network multilevel coordination as a key dynamic for IOL to evolve to NL.